Method for producing polyester film using biomass resource-derived polyester resin, and polyester film

By using aluminum compound and phosphorus compound catalysts to polycondensate and combined with 5-50% recovery polyester resin, polyester film is prepared, which solves the problem of film characteristics fluctuations caused by the change in the amount of the recovered polyester film, and achieves stable film characteristics and environmentally friendly effects.

CN119894960APending Publication Date: 2025-04-25TOYOBO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380066077.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-22
Filing Date
2023-09-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When using polyester films to make use of polyethylene terephthalate produced from biomass resources, changes in the amount of the recovered polyester film cause fluctuations in film characteristics, making it difficult to ensure stability of quality.

Method used

Polycondensation was performed using aluminum compounds and phosphorus compounds as catalysts to prepare a polyester film containing 5 to 50% of the recovered polyester resin, and the mechanical and chemical characteristics of the film were ensured by controlling the intrinsic viscosity and acid value.

Benefits of technology

Even if the amount of the recovered polyester film is added to the change, the various characteristics of the obtained polyester film do not change greatly, ensuring the stability of the film quality and improving the effect of reducing environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005310949720000071
    Figure BDA0005310949720000071
  • Figure BDA0005310949720000081
    Figure BDA0005310949720000081
  • Figure BDA0005310949720000091
    Figure BDA0005310949720000091
Patent Text Reader

Abstract

A polyester film containing a polyethylene terephthalate produced using ethylene glycol derived from a biomass resource or terephthalic acid derived from a biomass resource, the polyethylene terephthalate produced from a monomer derived from a biomass resource is obtained by polycondensation of an aluminum compound and a phosphorus compound using as a catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a polyester film using a polyester resin produced using a monomer derived from a biomass resource, and the obtained polyester film. Background Art

[0002] Polyester films are widely used as packaging and industrial parts because they can be excellent in mechanical strength, chemical stability, heat resistance, and moisture resistance, and further have improved transparency, and can be stably supplied at a low price.

[0003] The most commonly used polyester film is polyethylene terephthalate, which is a polycondensate of terephthalic acid and ethylene glycol. Terephthalic acid and ethylene glycol are produced from petroleum, which is a fossil fuel. In recent years, the world needs to promote alternatives based on biomass resources, in view of the global environmental problems such as the fear of the depletion of fossil fuel resources and the increase of carbon dioxide in the atmosphere.

[0004] The production of ethylene glycol using biomass resources includes a method of producing ethanol from sugar cane, bagasse, carbohydrate crops, etc. by biological treatment, and further producing a mixture of ethylene glycol, diethylene glycol, and triethylene glycol through ethylene oxide, etc. The production of terephthalic acid using biomass resources includes, for example, a method of rapidly thermally decomposing biomass resources such as wood chips using a catalyst to produce xylene, then separating and purifying and isomerizing to produce p-xylene, and then subjecting the p-xylene to a liquid phase oxidation reaction to produce terephthalic acid.

[0005] In order to reduce the environmental burden, the use of polyethylene terephthalate produced from monomers using biomass resources is being studied in polyester films. Many of these films that cope with environmental burdens have products that guarantee the degree of environmental burden they cope with, such as having a biomass content of a certain amount or more.

[0006] On the other hand, in the manufacture of polyester film, not all the polyester resins put in for the manufacture will form films in the portion clamped by the tenter clip during the lateral stretching and in the film that is not suitable for shipment until the manufacturing conditions are stabilized and the product can be taken out. Although there are cases where the recycled polyester resins obtained from the film manufacturing process are reused as raw materials for the manufacture of films, they are once placed in a high-temperature environment after being melted, and decompose, resulting in a decrease in molecular weight and an increase in terminal carboxyl groups. In order to stabilize the quality of the film using such recycled polyester resins, it is preferred to add a certain amount of recycled polyester resins frequently, but a certain amount of recycled polyester resins is not always produced in the manufacture of films, and a certain amount is not always produced, so the recycled polyester resins are mostly recycled polyester resins collected from multiple production lines and polyester resins collected from products of different brands.

[0007] However, in the film to cope with the environmental burden, due to the above-mentioned restrictions, it is necessary not to randomly mix resins other than those derived from biomass resources into the recycled polyester resin, and it is difficult to ensure a certain amount of recycled polyester resin. It is not possible to stably and continuously produce a certain amount, and it is difficult to avoid fluctuations in the amount of recycled polyester resin added when there are short-term fluctuations in production.

[0008] In view of such circumstances, in a film made of polyethylene terephthalate obtained from a monomer derived from a biomass resource, it is required that various properties of the obtained film do not change significantly even if the amount of the recycled polyester film added is changed. Prior art literature Patent Literature

[0009] Patent document 1: WO2022 / 131360 Summary of the invention Problem that the invention aims to solve

[0010] The present invention is made against the background of such problems in the prior art. That is, the purpose of the present invention is to provide a polyester film and a method for producing the same, wherein various properties of the obtained film do not change significantly even if the amount of recycled polyester film added is changed in the film made of polyethylene terephthalate obtained from monomers derived from biomass resources. Means of solving the problem

[0011] The present invention is constituted as follows.

[0012] [1] A polyester film comprising polyethylene terephthalate obtained using ethylene glycol derived from biomass resources and / or terephthalic acid derived from biomass resources, wherein the polyethylene terephthalate obtained from monomers derived from biomass resources is polycondensed using an aluminum compound and a phosphorus compound as a catalyst.

[0013] [2] The polyester film according to [1], wherein the polyester film contains a recycled polyester resin obtained in a film production process.

[0014] [3] The polyester film according to [2], wherein the ratio of the recovered polyester film is 5 to 50% by mass of the total polyester resin constituting the film.

[0015] [4] The polyester film according to any one of [1] to [3], wherein the intrinsic viscosity of the polyester resin constituting the film is 0.52 to 0.73 dL / g.

[0016] [5] The polyester film according to any one of [1] to [3], wherein the acid value of the polyester resin constituting the film is 5 to 80 dL / g.

[0017] [6] A method for producing a polyester film, characterized in that it is a method for producing a polyester film comprising a step of producing a polyester film using polyethylene terephthalate obtained from ethylene glycol derived from biomass resources and / or terephthalic acid derived from biomass resources as a raw material, and unused polyethylene terephthalate obtained from the monomer derived from biomass resources and recycled polyethylene terephthalate which is a molten molded product discharged from the polyester film production step are melt-mixed to form a film.

[0018] [7] The method for producing a polyester film according to [6], wherein the amount of the recycled polyethylene terephthalate is 5 to 50% by mass relative to the total amount of the unused polyethylene terephthalate produced from monomers derived from biomass resources and the recycled polyethylene terephthalate.

[0019] [8] The method for producing a polyester film according to [6] or [7], wherein the polyethylene terephthalate produced from monomers derived from biomass resources contains an aluminum compound and a phosphorus compound as catalysts.

[0020] [9] The method for producing a polyester film according to [6] or [7], wherein the difference between the intrinsic viscosity of the unused polyethylene terephthalate produced from monomers derived from biomass resources and the intrinsic viscosity of the recovered polyethylene terephthalate is 0.1 dL / g or less.

[0021]

[10] The method for producing a polyester film according to [6] or [7], wherein the ratio of the intrinsic viscosity of the unused polyethylene terephthalate produced from monomers derived from biomass resources to the intrinsic viscosity of the recovered polyethylene terephthalate is 0.85 to 1. Effects of the Invention

[0022] According to the present invention, a polyester film can be obtained in which the various properties of the obtained film do not change significantly even if the amount of recycled polyester film added is changed in a film made from polyethylene terephthalate obtained from monomers derived from biomass resources as a raw material. Even if the output is changed, a film with stable quality can be supplied, and the effect of reducing the burden on the environment can be further improved. DETAILED DESCRIPTION

[0023] In the present invention, polyethylene terephthalate obtained from monomers derived from biomass resources is melted and formed to form a polyester film. In addition, in the following, polyethylene terephthalate may be referred to as PET, and polyethylene terephthalate obtained from monomers derived from biomass resources may be referred to as Bio PET.

[0024] Bio PET is a material in which a monomer using biomass resources is used in at least one of ethylene glycol and terephthalic acid. In particular, it is preferred that PET using ethylene glycol derived from biomass resources is used for ethylene glycol, and ethylene glycol is preferably 50% or more derived from biomass resources, more preferably 60% or more, further preferably 70% or more, particularly preferably 80% or more, and most preferably 90% or more derived from biomass resources, and may also be 100% by mass. In addition, the same is true when terephthalic acid derived from biomass resources is used.

[0025] Bio PET may also contain copolymer components other than ethylene glycol and terephthalic acid components. As diol components other than ethylene glycol, there may be mentioned: diethylene glycol, neopentyl glycol, trimethylene glycol, tetramethylene glycol, 1,5-pentanediol, 1,6-hexanediol, cyclohexanedimethanol, bisphenol A, S, EO, PO adducts of F. As dicarboxylic acid components other than terephthalic acid, there may be mentioned: isophthalic acid, naphthalene dicarboxylic acid, adipic acid, sebacic acid, cyclohexane dicarboxylic acid, etc. When the total diol component and the total dicarboxylic acid component are 100 mol%, the amount of the copolymer components is preferably 5 mol% or less, more preferably 4 mol% or less, and further preferably 3 mol% or less. In addition, diethylene glycol may be 10 mol% or less, or 7 mol% or less. The total amount of the copolymer components is preferably 5 mol% or less, more preferably 4 mol% or less, further preferably 3 mol% or less, and particularly preferably 2.5 mol% or less in the total excluding diethylene glycol. The total amount of the polymer components including the diethylene glycol component is preferably 10 mol% or less, more preferably 7 mol% or less.

[0026] The polyester film may be a single layer or a multi-layer film. In the case of a multi-layer film, it is preferred that at least one layer contains PET derived from biomass resources. In the PET constituting the polyester film, Bio PET is preferably 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, more preferably more than 95% by mass, further preferably more than 96% by mass, particularly preferably more than 97% by mass, and most preferably 100% by mass. In addition, the carbon content derived from biomass resources measured by radiocarbon (C14) is preferably 14% or more on a molar basis (based on atomic number) with respect to the total carbon of the PET constituting the polyester film, more preferably 16% or more, further preferably 18% or more, particularly preferably 19% or more, and most preferably more than 19%. In the case of using only ethylene glycol derived from biomass resources in ethylene glycol, the theoretical upper limit of the carbon content derived from biomass resources is 20%. When terephthalic acid derived from biomass resources is also used as terephthalic acid, the carbon content derived from biomass resources may exceed 20%. Since a high carbon content is preferred, the most preferred value is 100%, and it may be 95% or less, 90% or less, 80% or less, or 70% or less.

[0027] It is known that since C14 is contained in a certain proportion (105.5 pMC) in carbon dioxide in the atmosphere, the C14 content in plants that absorb carbon dioxide in the atmosphere, such as corn, is also about 105.5 pMC. In addition, it is also known that fossil fuels contain almost no C14. Therefore, by measuring the proportion of C14 contained in the total carbon atoms in polyester, the proportion of carbon atoms derived from biomass resources can be calculated. The carbon content derived from biomass resources can be measured, for example, by radiocarbon (C14) measurement shown in ASTM D6866-16 Method B (AMS).

[0028] As a catalyst for producing Bio PET, any catalyst commonly used can be used without limitation. For example, antimony compounds, titanium compounds, germanium compounds, composite catalysts of aluminum compounds and phosphorus compounds can be mentioned. Among them, antimony compounds and aluminum compounds are preferred because the resulting PET has high thermal stability. As a representative example of antimony compounds, antimony trioxide can be mentioned.

[0029] The lower limit of the amount of the antimony compound added is preferably 50 mass ppm, more preferably 80 mass ppm, and further preferably 100 mass ppm, based on the content of the antimony element in the obtained Bio PET. By setting it to above, an economical polymerization rate can be ensured. The upper limit of the content of the antimony element is preferably 330 mass ppm, more preferably 300 mass ppm, further preferably 270 mass ppm, particularly preferably 250 mass ppm, and most preferably 230 mass ppm. By setting it to below the above, the decomposition of the recycled resin can be suppressed.

[0030] Examples of the composite catalyst of an aluminum compound and a phosphorus compound include the following catalysts.

[0031] (Aluminum compounds) The aluminum compound is not limited as long as it is a compound soluble in a solvent, and known aluminum compounds can be used without limitation. Among these, at least one selected from carboxylates, inorganic acid salts and chelates is preferred. Among these, at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, basic aluminum chloride and aluminum acetylacetonate is more preferred, at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, basic aluminum chloride and aluminum acetylacetonate is further preferred, at least one selected from aluminum acetate and basic aluminum acetate is particularly preferred, and basic aluminum acetate is most preferred.

[0032] From the viewpoint of fully exerting the polymerization activity and suppressing the increase in the amount of aluminum-based foreign matter, the amount of the aluminum compound added is preferably 5 to 50 mass ppm, more preferably 7 to 40 mass ppm, further preferably 10 to 30 mass ppm, and particularly preferably 15 to 25 mass ppm, based on the content of the aluminum element in Bio PET.

[0033] In addition, when cost is important, the content of aluminum in Bio PET is preferably 9 to 20 mass ppm, more preferably 9 to 19 mass ppm, further preferably 10 to 17 mass ppm, and particularly preferably 12 to 17 mass ppm. By making the aluminum content 9 mass ppm or more, the polymerization activity can be fully exerted. On the other hand, by setting it to 20 mass ppm or less, from the relationship with the content of phosphorus described later, the increase in the amount of aluminum-based foreign matter can be avoided, and the increase in the cost of the catalyst can also be suppressed.

[0034] (Phosphorus compounds) The phosphorus compound is not particularly limited, but phosphonic acid compounds and phosphinic acid compounds are preferably used because they have a large effect of improving the catalytic activity. Among these, phosphonic acid compounds are more preferably used because they have a particularly large effect of improving the catalytic activity.

[0035] Among the above-mentioned phosphorus compounds, phosphorus compounds having a phosphorus element and a phenol structure in the same molecule are preferred. There are no particular limitations on the phosphorus compounds as long as they have a phosphorus element and a phenol structure in the same molecule, but when one or more compounds selected from the group consisting of phosphonic acid compounds having a phosphorus element and a phenol structure in the same molecule and phosphinic acid compounds having a phosphorus element and a phenol structure in the same molecule are used, it is preferred because the effect of improving the catalytic activity is large, and when one or more phosphonic acid compounds having a phosphorus element and a phenol structure in the same molecule are used, it is more preferred because the effect of improving the catalytic activity is very large.

[0036] In addition, examples of phosphorus compounds having a phosphorus element and a phenol structure in the same molecule include P(=O)R 1 (OR 2 )(OR 3 )、P(=O)R 1 R 4 (OR 2 ) represented by the compound, etc. 1 R represents a hydrocarbon group having 1 to 50 carbon atoms containing a phenolic moiety, or a hydrocarbon group having 1 to 50 carbon atoms containing a substituent such as a hydroxyl group, a halogen group, an alkoxy group, or an amino group and a phenolic structure. 4 R represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms which has a substituent such as a hydroxyl group, a halogen group, an alkoxy group, or an amino group. 2 , R 3 Each independently represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms containing a substituent such as a hydroxyl group or an alkoxy group. The hydrocarbon group may also contain a branched structure, an alicyclic structure such as a cyclohexyl group, or an aromatic ring structure such as a phenyl group or a naphthyl group. 2 With R 4 The ends of the nucleotides can also form bonds.

[0037] Examples of the phosphorus compound having a phosphorus element and a phenol structure in the same molecule include p-hydroxyphenylphosphonic acid, dimethyl p-hydroxyphenylphosphonate, diethyl p-hydroxyphenylphosphonate, diphenyl p-hydroxyphenylphosphonate, bis(p-hydroxyphenyl)phosphinic acid, methyl bis(p-hydroxyphenyl)phosphinic acid, phenyl bis(p-hydroxyphenyl)phosphinic acid, p-hydroxyphenylphosphinic acid, methyl p-hydroxyphenylphosphinic acid, and phenyl p-hydroxyphenylphosphinic acid.

[0038] As the phosphorus compound having a phosphorus element and a phenol structure in the same molecule, in addition to the phosphorus compounds exemplified above, there can be mentioned a phosphorus compound having a phosphorus element and a hindered phenol structure (a phenol structure in which an alkyl group having a tertiary carbon (preferably an alkyl group having a tertiary carbon at a benzyl position, such as a tert-butyl group, a tert-hexyl group, or a neopentyl group) is bonded to one or two ortho positions of a hydroxyl group) in the same molecule, and preferably a phosphorus compound having a phosphorus element and a structure of the following (chemical formula A) in the same molecule, and more preferably 3,5-di-tert-butyl-4-hydroxybenzyl dialkylphosphonate represented by the following (chemical formula B). In addition, as the phosphorus compound used for producing the polyester resin (B), 3,5-di-tert-butyl-4-hydroxybenzyl dialkylphosphonate represented by the following (chemical formula B) is preferred, but in addition thereto, a modified form of 3,5-di-tert-butyl-4-hydroxybenzyl dialkylphosphonate may be included. Details of the modified form will be described later.

[0039] [Chemistry 1]

[0040] (In (chemical formula A), * represents an atomic bond.)

[0041] [Chemistry 2]

[0042] (In (chemical formula B), X 1 , X 2 Each represents hydrogen or an alkyl group having 1 to 4 carbon atoms. )

[0043] In this specification, a polyester resin in which at least one hindered phenol structure can be detected by the P-NMR measurement method of a solution dissolved in a hexafluoroisopropanol-based solvent is referred to as "having a hindered phenol structure". That is, Bio PET is preferably a polyester resin produced using a phosphorus compound having a phosphorus element and a hindered phenol structure in the same molecule as a polymerization catalyst. The method for detecting the hindered phenol structure in PET (P-NMR measurement method) will be described later.

[0044] In the above (chemical formula B), preferably X 1 , X 2 All of them are alkyl groups having 1 to 4 carbon atoms, and more preferably alkyl groups having 1 to 2 carbon atoms. In particular, an ethyl ester having 2 carbon atoms is commercially available as Irganox 1222 (manufactured by BASF), and is preferred because it is easily available.

[0045] The phosphorus compound is preferably used by heat treatment in a solvent. In addition, the details of the heat treatment are described later. As the phosphorus compound, when using 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester as a phosphorus compound shown in (chemical formula B), in the above-mentioned heat treatment, a part of the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester as a phosphorus compound shown in (chemical formula B) undergoes structural changes. For example, the change is the detachment of the tert-butyl group, the hydrolysis of the ethyl ester group, and the hydroxyethyl ester exchange structure (ester exchange structure with ethylene glycol). Therefore, in the present invention, as a phosphorus compound, in addition to the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester shown in (chemical formula B), a phosphorus compound with a changed structure is also included. In addition, the detachment of the tert-butyl group occurs significantly at high temperatures in the polymerization process.

[0046] Hereinafter, 9 phosphorus compounds in which a part of the structure of diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate is changed are shown when diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate is used as the phosphorus compound. The amount of each phosphorus compound in which the structure is changed in the diol solution can be quantified by the P-NMR measurement method.

[0047] [Chemistry 3]

[0048] Therefore, the phosphorus compound in the present invention may contain, in addition to 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester, 9 modified forms of 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester represented by the above chemical formula.

[0049] When Irganox 1222 is used as the phosphorus compound, the polyester resin contains 9 types of phosphorus compound residues shown in Table 1 below. When at least one of the 9 types of hindered phenol structures shown in Table 1 is detected by P-NMR measurement, the polyester resin (B) can be said to be a polyester resin produced using a phosphorus compound having a phosphorus element and a hindered phenol structure in the same molecule as a polymerization catalyst. By using a phosphorus compound having a hindered phenol structure, it is possible to suppress the cost of the catalyst while exhibiting sufficient polymerization activity.

[0050] [Table 1]

[0051] Example of determination of the presence of hindered phenol structure or its decomposition residue 420 mg of the sample was dissolved in 2.7 mL of a mixed solvent of hexafluoroisopropanol and heavy benzene at a ratio of 1:1 (mass ratio), 10 μL of a 25% phosphoric acid solution in acetone was added, and centrifugation was performed. Then, 100 to 150 mg of trifluoroacetic acid was added to the supernatant, and P-NMR measurement was immediately performed under the following conditions. Apparatus: Fourier transform nuclear magnetic resonance apparatus (made by BRUKER, AVANCE500) 31P resonance frequency: 202.456MHz Locking solvent: heavy benzene Detection pulse tilt angle: 65° Data acquisition time: 1.5 seconds Delay time: 0.5 seconds Proton decoupling: Complete decoupling Measuring temperature: 25~35℃ Scan times: about 20,000 to 30,000 times The peak wavelengths of the residues of the chemical formula numbers shown in Table 1 are shown below. When these peak wavelengths are detected, it can be determined that the sample has a hindered phenol structure. Chemical formula 1: 34.5ppm, Chemical formula 4: 30.5ppm, Chemical formula 7: 53.6ppm Chemical formula 2: 33.8ppm, Chemical formula 5: 30.1ppm, Chemical formula 8: 53.0ppm Chemical formula 3: 31.9ppm, Chemical formula 6: 28.7ppm, Chemical formula 9: 51.3ppm

[0052] In the present invention, it is preferred that at least one of the above Chemical Formulas 1, 4 and 7 is contained.

[0053] From the viewpoint of exerting polymerization activity, suppressing the increase in the amount of aluminum-based foreign matter, and suppressing costs, the content of phosphorus in Bio PET is preferably 5 to 1000 mass ppm, more preferably 10 to 500 mass ppm, further preferably 15 to 200 mass ppm, particularly preferably 20 to 100 mass ppm, and most preferably 30 to 50 mass ppm.

[0054] When cost is given greater importance, the content of phosphorus in Bio PET is preferably 13 to 31 mass ppm, more preferably 15 to 29 mass ppm, and even more preferably 16 to 28 mass ppm.

[0055] From the same viewpoint as above, the molar ratio of phosphorus to aluminum in Bio PET is preferably 1.00 to 5.00, more preferably 1.10 to 4.00, further preferably 1.20 to 3.50, and particularly preferably 1.25 to 3.00. As described above, the aluminum and phosphorus in Bio PET are each derived from an aluminum compound and a phosphorus compound used as a polymerization catalyst. By using these aluminum compounds and phosphorus compounds in combination at a specific ratio, a complex with catalytic activity is functionally formed in the polymerization system, and sufficient polymerization activity can be exerted. In addition, although the resin manufactured using a polymerization catalyst composed of an aluminum compound and a phosphorus compound has an increased catalyst cost (increased manufacturing cost) compared to a polyester resin manufactured using a catalyst such as an antimony catalyst, by using an aluminum compound and a phosphorus compound in combination at a specific ratio, it is possible to suppress the cost of the catalyst while exerting sufficient polymerization activity. When cost is given priority, the residual molar ratio of phosphorus element to aluminum element is preferably 1.32 to 1.80, and more preferably 1.38 to 1.68.

[0056] Bio PET is melted, mixed and formed into a film. In the film forming, not all the amount of resin put in is shipped as a product. For example, process recycles such as scraps at the ends, end materials at the slits, and films until stable production are produced. In order to save resources and maintain the environment, reduce costs, etc., there are cases where the recycles from these processes are not discarded but reused as raw material resins. In particular, in the case of a PET film stretched in the width direction by a tenter, a large amount of process recycles are produced because the clamp part of the tenter is not stretched.

[0057] In the present invention, such process recycling products are preferably mixed with unused Bio PET and reused as raw materials for film manufacturing. In addition, there are films that are not shipped because their characteristics do not fall within the determined specifications, and films that are returned due to complaints, etc., and it is preferred that these are also mixed with process recycling products and reused. In the following, there are cases where PET recycled from the process is called recycled PET, and unused Bio PET is called virgin PET. In addition, unused means that after the manufacturing PET is remade into pellets, etc., it has not been melted and solidified again. Recycled PET may be crushed and fed directly into a film production facility, but in order to stabilize the amount fed and to suppress segregation from virgin PET in a hopper, it is preferably remelted and pelletized.

[0058] In the present invention, in the production of the film, it is preferred to use virgin PET of Bio PET and recycled PET generated in the film production process of Bio PET as the raw material PET.

[0059] The lower limit of the ratio of recycled PET to the total raw material resin in the film manufacturing is preferably 5% by mass, more preferably 10% by mass, and further preferably 15% by mass. The upper limit of the ratio of recycled PET is preferably 50% by mass, more preferably 40% by mass, and further preferably 35% by mass. By setting it within the above range, it is possible to achieve stable production and quality stability of raw materials.

[0060] In the manufacture of the film, all the raw material PET used may not be Bio PET, but may include PET derived from two existing fossil fuels, terephthalic acid and ethylene glycol. In particular, in the manufacture of the film, when adding lubricant particles, resistivity regulators, pigments, ultraviolet absorbers, etc., although there is a case of mixing as a masterbatch, it is not necessary to use Bio PET even in the PET used for the masterbatch. By sharing it with the usual PET film, economical production can be sought.

[0061] In the production of the film, the raw material PET may not be entirely PET, but may contain copolyester or other resins depending on the application, etc. The specific copolyester or other resins are described using the following examples of application. In such a case, even if the resin recovered from the film production process contains resins other than PET, it is set to fall within the scope of recovered PET.

[0062] The lower limit of the ratio of the amount of Bio PET to the total resin constituting the film is preferably 20% by mass, more preferably 30% by mass, further preferably 50% by mass, particularly preferably 70% by mass, and most preferably 80% by mass. By setting the ratio to be greater than the above lower limit, environmental compatibility can be improved.

[0063] Such recycled PET has a lower molecular weight or an increased amount of terminal carboxyl groups compared to virgin PET. As an indicator of molecular weight, it is preferred to use intrinsic viscosity, referred to as IV, and the amount of terminal carboxyl groups is referred to as AV, and the cyclic trimer is referred to as CT. Even in the case where the amount of recycled PET added varies depending on the production lot, in order to reduce the quality variation between lots, it is preferable to set the IV difference, AV difference, etc. between virgin PET and recycled PET within a specific range.

[0064] The lower limit of the difference between the IV of virgin PET and recycled PET is preferably 0.01 dL / g, more preferably 0.02 dL / g. The upper limit of the difference between the IV of virgin PET and recycled PET is preferably 0.1 dL / g, more preferably 0.08 dL / g, further preferably 0.07 dL / g, particularly preferably 0.065 dL / g, and most preferably 0.06 dL / g.

[0065] The lower limit of the value of IV of recycled PET / IV of virgin PET, which is the ratio of IV of recycled PET to IV of virgin PET, is preferably 0.85, more preferably 0.87, further preferably 0.88, particularly preferably 0.89, and most preferably 0.9. The upper limit of IV of recycled PET / IV of virgin PET is preferably 0.99, more preferably 0.98, on a practical level.

[0066] The AV difference between virgin PET and recycled PET is preferably 3 eq / ton, more preferably 4 eq / ton, and further preferably 5 eq / ton. The upper limit of the AV difference between virgin PET and recycled PET is preferably 22 eq / ton, more preferably 20 eq / ton, further preferably 17 eq / ton, particularly preferably 15 eq / ton, and most preferably 13 eq / ton.

[0067] By setting the IV difference between virgin PET and recycled PET, the value of IV of recycled PET / IV of virgin PET, and the AV difference between virgin PET and recycled PET within the above range, it is possible to ensure the quality stability of the product even when the amount of recycled resin added varies depending on the production batch. In addition, the above means on a practical level that the recycled PET is not subjected to solid phase polymerization, or is not subjected to dehydration polymerization reaction under reduced pressure after remelting, and even if the reaction is carried out, strict management is not required. Furthermore, there is no complicated means such as classifying the recycled PET according to IV and selecting it in combination with the IV of virgin PET, and it can be achieved economically in a simple way.

[0068] CT in PET is an equilibrium reaction, and its content is basically determined by the resin temperature. Therefore, when both virgin PET and recycled PET are not subjected to solid phase polymerization, the CT content is almost the same. In this case, the upper limit of the difference in CT content between virgin PET and recycled PET is preferably 0.1% by mass, and more preferably 0.08% by mass. On the other hand, when the virgin PET is solid-phase polymerized, the CT content decreases. In this case, the recycled PET can also be solid-phase polymerized, and the lower limit of the difference in CT content between the virgin PET and the recycled PET is preferably 0% by mass, more preferably 0.02% by mass, and further preferably 0.05% by mass. The upper limit of the difference in CT content between the virgin PET and the recycled PET is preferably 0.4% by mass, more preferably 0.3% by mass, further preferably 0.2% by mass, and particularly preferably 0.15% by mass.

[0069] In order to make the difference in IV, AV, and CT content between virgin PET and recycled PET within the above range, it is preferred that the IV, AV, and CT content of virgin PET be within a specific range. The lower limit of the IV of virgin PET is preferably 0.54 dL / g, more preferably 0.56 dL / g, further preferably 0.57 dL / g, and particularly preferably 0.58 dL / g. By setting it above the above lower limit, it is possible to easily reduce the IV difference and AV difference between virgin PET and recycled PET while ensuring the mechanical properties of the obtained film, and it is easy to suppress the change of mechanical properties and ensure film stability. The upper limit of the IV of virgin PET is preferably 0.75 dL / g, more preferably 0.70 dL / g, further preferably 0.68 dL / g, particularly preferably 0.66 dL / g, and most preferably 0.65 dL / g. By setting it below the above upper limit, it is possible to easily suppress the deterioration of the recycled resin while ensuring film stability, and it is easy to reduce the IV difference and AV difference between virgin PET and recycled PET. In addition, when it is below 0.68 dL / g, only melt polymerization can be carried out, which is economically advantageous.

[0070] From the perspective of productivity, the lower limit of AV of virgin PET is preferably 1 eq / ton, more preferably 3 eq / ton, and further preferably 5 eq / ton. When PET is produced only by melt polymerization, the lower limit is preferably 10 eq / ton, and more preferably 15 eq / ton. When the AV is above 10 eq / ton, only melt polymerization can be performed, which is economically advantageous. The upper limit of AV of virgin PET is preferably 70 eq / ton, more preferably 60 eq / ton, further preferably 55 eq / ton, and particularly preferably 50 eq / ton. By setting it below the upper limit, it is easy to suppress the degradation of the recycled resin.

[0071] From the perspective of productivity, the lower limit of the CT amount of virgin PET is preferably 0.3% by mass, more preferably 0.5% by mass, further preferably 0.7% by mass, and particularly preferably 0.8% by mass. The upper limit of the CT amount of virgin PET is preferably 1.1% by mass, more preferably 1.05% by mass, and further preferably 1% by mass. By setting it below the above upper limit, it can be carried out. When PET is produced only by melt polymerization, the CT amount is about 0.9 to 1.0% by mass.

[0072] The lower limit of IV of recycled PET is preferably 0.5 dL / g, more preferably 0.51 dL / g, and further preferably 0.52 dL / g. By setting the lower limit or more, it is possible to easily reduce the IV difference and AV difference between virgin PET and recycled PET while ensuring the mechanical properties of the obtained film, and it is easy to suppress the fluctuation of mechanical properties and ensure the stability of film production. The upper limit of IV of recycled PET is preferably 0.72 dL / g, more preferably 0.68 dL / g, further preferably 0.66 dL / g, particularly preferably 0.64 dL / g, and most preferably 0.63 dL / g. By setting it below the above upper limit, it is possible to easily reduce the IV difference and AV difference between virgin PET and recycled PET while ensuring film production stability. In addition, when it is below the above upper limit, solid phase polymerization of recycled PET is not performed, or even if it is performed, it can be performed in a short time, which is advantageous in terms of cost.

[0073] The lower limit of the AV of the recycled PET is preferably 3 eq / ton, more preferably 5 eq / ton, further preferably 10 eq / ton, particularly preferably 15 eq / ton, and most preferably 20 eq / ton. If it is above the above lower limit, there is no need to perform solid phase polymerization on the recycled PET, or even if solid phase polymerization is performed, it can be performed in a short time, which is advantageous in terms of cost. The upper limit of the AV of the recycled PET is preferably 85 eq / ton, more preferably 80 eq / ton, further preferably 75 eq / ton, particularly preferably 70 eq / ton, and most preferably 65 eq / ton. By setting it below the above upper limit, the resin degradation when the film is produced by adding the recycled resin can be suppressed.

[0074] The lower limit of the CT amount of the recycled PET is preferably 0.5% by mass, more preferably 0.7% by mass, and further preferably 0.8% by mass. The upper limit of the CT amount of the recycled PET is preferably 1.1% by mass, more preferably 1.05% by mass, and further preferably 1% by mass. When a film made of only melt-polymerized PET is used as the recycled PET, the CT amount is about 0.9 to 1.0% by mass.

[0075] Among the total raw material PET for manufacturing the film, the lower limit of the proportion of recycled PET is preferably 5% by mass, more preferably 10% by mass, and further preferably 15% by mass. The upper limit of the proportion of recycled PET is preferably 50% by mass, more preferably 40% by mass, and further preferably 35% by mass. By controlling within the above range, it is possible to ensure stable production of recycled raw materials and quality stability of the resulting film.

[0076] When manufacturing a film, it is preferred to make PET as difficult to decompose as possible. For example, the water content of the PET used as a raw material is reduced, the resin temperature during melt mixing is reduced, and the time the resin is in a molten state is shortened, as described below.

[0077] When manufacturing the film, the lower limit of the water content of the virgin PET and the recycled TET used as the raw materials is preferably 1 mass ppm, more preferably 5 mass ppm, and further preferably 10 mass ppm. When manufacturing the film, the upper limit of the water content is preferably 150 mass ppm, more preferably 100 mass ppm, further preferably 70 mass ppm, particularly preferably 50 mass ppm, and most preferably 30 mass ppm. By setting it below the above upper limit, the resin decomposition in the manufacturing process of the film can be suppressed, and the degradation of the recycled resin can be suppressed.

[0078] The lower limit of the melting temperature of the resin when manufacturing the film is the temperature at the highest point, preferably 270°C, more preferably 275°C. By setting it above the lower limit, productivity can be improved. The upper limit of the melting temperature is preferably 290°C, more preferably 288°C, further preferably 286°C, and particularly preferably 285°C. By setting it below the above upper limit, the resin decomposition in the manufacturing process of the film can be suppressed, and the degradation of the recycled resin can be suppressed. In addition, usually when manufacturing the film, the temperature of the resin in the second half of the extruder becomes high, which can be detected by the value of the thermometer equipped with the extruder.

[0079] The lower limit of the melting time of the resin when manufacturing the film is preferably 2 minutes, more preferably 3 minutes. The upper limit of the melting time of the resin when manufacturing the film is preferably 20 minutes, more preferably 15 minutes, further preferably minutes, particularly preferably minutes, and most preferably minutes. By setting it below the above upper limit, the degradation of the recycled resin can be suppressed.

[0080] Furthermore, in the step of pelletizing the recovered PET, it is also important to suppress the decomposition of PET.

[0081] The lower limit of the water content of the recycled PET when pelletized is preferably 1 mass ppm, more preferably 5 mass ppm, and further preferably 10 mass ppm. The upper limit of the water content of the recycled PET when pelletized is preferably 150 mass ppm, more preferably 100 mass ppm, further preferably 70 mass ppm, particularly preferably 50 mass ppm, and most preferably 30 mass ppm. By setting it below the above upper limit, the deterioration of the recycled PET can be suppressed. When the recovered PET is an edge portion during film production, it is preferred to pelletize the edge portion immediately after cutting it off.

[0082] The lower limit of the melting temperature of the pelletized recycled PET is the temperature at which the temperature becomes the highest, preferably 270°C, more preferably 275°C. By setting it to be above the above lower limit, productivity can be improved. The upper limit of the melting temperature of the pelletized recycled PET is preferably 290°C, more preferably 288°C, further preferably 286°C, and particularly preferably 285°C. By setting it below the above upper limit, the deterioration of the recycled resin can be suppressed. In addition, in the second half of the extruder, the temperature of the resin becomes the highest, which can be detected by the value of the thermometer equipped with the extruder.

[0083] The lower limit of the melting time when the recycled PET is pelletized is preferably 1 minute, and more preferably 2 minutes. The upper limit of the melting time when the recycled PET is pelletized is preferably 15 minutes, and more preferably 10 minutes. By setting it below the above upper limit, the degradation of the recycled resin can be suppressed.

[0084] In pelletizing the recycled PET, it is also a preferred method to use an extruder with a discharge port and perform melt kneading while reducing the pressure.

[0085] In addition, by subjecting recycled PET to solid phase polymerization, the decreased molecular weight can be increased. However, except for the purpose of obtaining a film with high IV, low AV, and low CT that cannot be obtained when PET is melt-polymerized, it is not necessarily preferred to subject recycled PET to solid phase polymerization from an economic perspective.

[0086] In the manufacture of the film, the molten resin is preferably extruded into a sheet-like shape, and the resulting unstretched sheet-like object is stretched in at least one direction after cooling. In the stretching, a roller stretching method is preferably used when the film is stretched in the longitudinal direction, and a tenter stretching is preferably used when the film is stretched in the transverse direction. In addition, a tenter can also be used to perform biaxial stretching in both the longitudinal and transverse directions. The stretching temperature is preferably 80 to 130° C., more preferably 85 to 120° C., in both the longitudinal and transverse directions. The temperature can be adjusted within this range in accordance with the desired properties. The stretch ratio is preferably 3 to 8 times, more preferably 3.3 to 7 times, in at least one of the longitudinal and transverse directions of the main stretching direction, and can be adjusted in this temperature range in combination with the desired properties. Other stretch ratios can also be adjusted according to the properties required for the manufactured film.

[0087] The lower limit of the IV of the film is preferably 0.52 dL / g, more preferably 0.54 dL / g, further preferably 0.55 dL / g, and particularly preferably 0.56 dL / g. The upper limit of the IV of the film is preferably 0.73 dL / g, more preferably 0.70 dL / g, further preferably 0.67 dL / g, particularly preferably 0.65 dL / g, and most preferably 0.63 dL / g. By setting it to the above range, the film forming property can be improved while the mechanical properties are improved, and the decomposition of the recycled PET can be suppressed.

[0088] The lower limit of the AV of the film is preferably 5 eq / ton, more preferably 10 eq / ton. The upper limit of the AV of the film is preferably 80 eq / ton, more preferably 75 eq / ton, further preferably 70 eq / ton, particularly preferably 65 eq / ton, and most preferably 60 eq / ton. By setting it below the above upper limit, the decomposition of the recycled PET can be suppressed.

[0089] The lower limit of the CT amount of the film is preferably 0.5% by mass, more preferably 0.7% by mass, and still more preferably 0.8% by mass. The upper limit of the CT amount of the film is preferably 1.1% by mass, and more preferably 1.05% by mass.

[0090] The film may also contain anti-degradation agents such as colorants, lubricant particles, ultraviolet absorbers, melt resistivity regulators, antistatic agents, antioxidants, and heat stabilizers. As ultraviolet absorbers suitable for polyester films, cyclic imidate-based ultraviolet absorbers are preferred, and specific examples thereof include: 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazine-4-one), 2-methyl-3,1-benzoxazine-4-one, 2-butyl-3,1-benzoxazine-4-one, and 2-phenyl-3,1-benzoxazine-4-one.

[0091] As the anti-degradation agent, a compound having a hindered phenol structure is preferably used. In particular, when any one of an antimony compound, a germanium compound, and a titanium compound is used as a catalyst, the degradation of the recycled PET can be easily suppressed by adding a hindered phenol compound. As the hindered phenol compound, it is preferred to have the structure of (chemical formula A) above. Examples of these hindered phenol compounds include triethylene glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate], 1,6-hexanediol-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 2,2-diethylenethiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, These compounds are commercially available as Irganox(R). When a hindered phenol compound was used, the phenol part structure shown in Table 1 was detected in the polyester resin by P-NMR measurement.

[0092] Preferably, the hindered phenol compound is added so that the hindered phenol structure is preferably 0.03 equivalents / ton or more, more preferably 0.1 equivalents / ton or more, further preferably 0.17 equivalents / ton or more, particularly preferably 0.2 equivalents / ton or more, and most preferably 0.22 equivalents / ton or more relative to PET. In addition, it is preferably added so that the hindered phenol structure is 6.7 equivalents / ton or less, more preferably 3.4 equivalents / ton or less, further preferably 1.7 equivalents / ton or less, particularly preferably 1.5 equivalents / ton or less, and most preferably 1.4 equivalents / ton or less. The hindered phenol compound may be added during the polymerization of PET, or may be added to the PET after polymerization.

[0093] The film can be a single layer or a multilayer structure by coextrusion. In the case of a multilayer structure, the composition of each layer can be different, such as adding an ultraviolet absorber only to the middle layer and adding a lubricant only to the surface layer. In addition, the IV, AV, and CT amounts can also be different in each layer. When the membrane has a multi-layer structure, the IV, AV and CT values ​​of the membrane are values ​​measured as the entire membrane without separating the layers.

[0094] The polyester film is preferably surface treated in order to improve adhesion with adhesives, coating materials, inks, etc. Examples of the surface treatment include corona treatment, plasma treatment, and flame treatment.

[0095] The polyester film may also be provided with an easy-adhesion layer. The resin used for the easy-adhesive layer uses polyester resin, polyurethane resin, polycarbonate resin, acrylic resin, etc., preferably polyester resin, polyester polyurethane resin, polycarbonate polyurethane resin, acrylic resin. The easy-adhesive layer is preferably cross-linked. As a cross-linking agent, it can be enumerated: isocyanate compounds, melamine compounds, epoxy resins, oxazoline compounds, etc. In addition, in order to improve the adhesion with the polarizer, adding water-soluble resins such as polyvinyl alcohol is also a useful means.

[0096] The easy-adhesive layer can be provided by applying a water-based coating to which these resins and, if necessary, a crosslinking agent, particles, etc. are added on a polyester film and drying the coating. Examples of the particles include the particles used for the above-mentioned base material. The easy-adhesive layer can be provided offline on the stretched film, but is preferably provided inline in the film-making process. When provided inline, it can be provided before longitudinal stretching or transverse stretching, but it is preferably applied before transverse stretching, and dried and cross-linked in the preheating, heating, and heat treatment process of the tenter. In addition, when the inline coating is performed before longitudinal stretching by the roller, it is preferably introduced into the stretching roller after drying in a vertical dryer after coating. The coating amount of the adhesive layer is preferably 0.01 to 1.0 g / m 2 , more preferably 0.03 to 0.5 g / m 2 .

[0097] The polyester film can be used for various purposes as exemplified below. · Process release film: for example, a ceramic green sheet, a film made of a resin solution, etc. Transfer film: for example, metal foil, printed pattern layer, liquid crystal compound phase difference layer, liquid crystal compound polarizer, etc. The release film or the transfer film may further include a release layer made of a fluorine-based resin, a silicone-based resin, a long-chain alkyl-containing acrylic, a polyolefin, or the like.

[0098] · Protective film: For example, a polarizing plate protective film, a surface protective film of an image display device, a back protective film, a solar cell back sheet, etc. In these applications, an adhesive layer may also be provided. For example, an adhesive layer of a rubber-based, acrylic-based, silicone-based, urethane-based, etc. may also be provided on the protective film. In addition, when used as a permanent protective film such as a solar cell back sheet, it may also be a material that is attached to an object by an adhesive.

[0099] Optical film: For example, lens sheet substrate, prism sheet substrate, nanoimprint film substrate, diffusion sheet substrate, anti-scattering film, polarizer protective film, transparent conductive film substrate, etc. In optical films, there are cases where rainbow spots are generated due to the retardation of the polyester film and the light source. In order to suppress rainbow spots, the delay in the plane is preferably more than 3000nm, more preferably more than 4500nm, further preferably more than 6000nm, and particularly preferably more than 7000nm. In order to thin, the delay in the plane is preferably less than 30000nm, more preferably less than 15000nm, and further preferably less than 12000nm. At this time, the ratio (Re / Rth) of the delay in the plane (Re) to the delay in the thickness direction (Rth) is preferably more than 0.2, more preferably more than 0.5, more preferably more than 0.6, and particularly preferably more than 0.7. The upper limit of Re / Rth is 2, but from the viewpoint of suppressing the tearing of the film, it is preferably less than 1.5, more preferably less than 1.2, and more preferably less than 1.0.

[0100] Furthermore, in order to suppress rainbow spots, the NZ coefficient represented by |ny-nz| / |ny-nx| is preferably 2.5 or less, more preferably 2.2 or less, further preferably 2.0 or less, and particularly preferably 1.8 or less. The lower limit of the NZ coefficient is preferably 1.30 or more, more preferably 1.40 or more, and further preferably 1.50 or more. At this time, nx is the refractive index in the fast axis direction (Fast axis direction) in the plane, ny is the refractive index in the slow axis direction (slow axis direction) in the plane, and nz is the refractive index in the thickness direction. It is the refractive index in the direction perpendicular to the surface of the ester substrate film.

[0101] In addition, by reducing the delay in the plane, rainbow spots can also be suppressed. At this time, the delay in the plane is preferably less than 1000nm, more preferably less than 800nm, further preferably less than 500nm, and particularly preferably less than 400nm. The lower limit is 0nm, but from the perspective of stable production, it can be more than 10nm, more than 30nm, and more than 50nm. When reducing the delay in the plane, Re / Rth is preferably less than 0.1, more preferably less than 0.05. In addition, the NZ coefficient is preferably more than 10, more preferably more than 15, and more preferably more than 20.

[0102] Such high in-plane retardation films and low in-plane retardation films are suitable for films used in optical paths with a large amount of linear polarization in image display devices, etc. Examples thereof include polarizer protective films, transparent conductive film substrates for touch screens, etc., anti-scattering films, and surface protective films.

[0103] In lens, prism sheet, and nanoimprint, a layer of an acrylic compound provided on a polyester film can be brought into contact with a mold and cured to form a pattern. On the surface protection film of the image display device, the polarizer protection film, etc., a hard coating layer, an anti-reflection layer, an anti-reflection layer, an anti-glare layer, etc. can be provided. On the transparent conductive film, a hard coating layer, a refractive index adjustment layer, etc. can be provided. As the conductive layer of the transparent conductive film, ITO film, metal etching, mesh of conductive paste, coating layer of metal whisker, etc. can be cited.

[0104] Films for electrical, electronic and communication applications: for example, flexible circuit substrates, coverlay films, carrier tape covers, electronic tag substrates, IC cards, motor insulation films, etc.

[0105] Printing substrate film: such as electrical product labels, advertising labels, event labels, etc.

[0106] Barrier film: metal vapor-deposited film, metal oxide vapor-deposited film, barrier coating film, etc. Examples of metal vapor deposition include aluminum, examples of metal oxides include aluminum oxide, silicon dioxide, aluminum oxide-silicon composite oxides, and examples of barrier coatings include sol-gel coatings, coatings containing inorganic layered compound particles, polyvinyl alcohol coatings, ethylene-vinyl alcohol copolymer coatings, and vinyl chloride coatings.

[0107] ·Laminating film for packaging: lamination with nylon film, polypropylene film, etc. Heat-sealable films: lamination with heat-sealable layers of polyethylene, polypropylene, copolyester, etc. In these laminations, adhesives of isocyanate curing type, epoxy curing type, radiation curing type, etc. can be used.

[0108] Heat-shrinkable polyester film: beverage bottle labels, beverage can labels, cap seals, packaging of containers with lids, shrink packaging, etc. In these applications, in order to adjust the heat shrinkage characteristics, it is preferred to mix other polyesters or copolyester resins to form a film. Examples of other polyesters include tetramethylene terephthalate and trimethylene terephthalate, and examples of copolyesters include ethylene terephthalate isophthalate copolymers, ethylene butylene terephthalate copolymers, ethylene glycol 2,2-dimethylpropylene glycol terephthalate copolymers (those with neopentyl glycol added to the diol component), ethylene glycol 2,2'-oxydiethylene glycol copolymers (those with diethylene glycol added to the diol component), ethylene glycol 1,4-cyclohexanedimethanol terephthalate copolymers (those with 1,4-cyclohexanedimethanol added to the diol component), and polyesters obtained by copolymerizing these with other components. When the total acid components and the total glycol components in the film are respectively 100 mol%, the copolymerization amount and the mixing amount of the copolymer components other than the terephthalic acid component and the ethylene glycol component can be determined so that the total is preferably 5 to 70 mol%, more preferably 8 to 50 mol%, and further preferably 10 to 40 mol%.

[0109] The polyester film can also be made into a void-containing film by mixing and stretching the polyester resin with an incompatible resin such as polypropylene, polymethylpentene, polystyrene, etc. In this case, the incompatible resin is preferably 3 to 30% by mass, more preferably 5 to 20% by mass, relative to the total resin amount constituting the film. In addition, various pigments such as titanium oxide, barium sulfate, and carbon can be added to produce white, black, or other colored films. These films are preferably used for labels, printing films that replace paper, light reflective films, circuit substrates, cards, tags, and the like.

[0110] Furthermore, polyimide, polyamideimide, polyamide, polyphenylene sulfide, polyphenylene sulfone, polyphenylene ether, etc. may be added as modified polyester film. In this case, the modified resin other than polyester is preferably 0.5 to 20% by mass, more preferably 1 to 15% by mass, and further preferably 2 to 10% by mass relative to the total resin amount constituting the film. Example

[0111] The present invention will be described below by way of examples, but the present invention is not limited to these examples at all.

[0112] (1) Intrinsic viscosity (IV) About 3 g of the sample was freeze-pulverized, dried at 140°C for 15 minutes, and then 0.20 g was weighed and stirred at 100°C for 60 minutes in 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol at a mass ratio of 1:3 to completely dissolve. After cooling to room temperature, the sample was filtered through a glass filter. The falling time of the sample and the solvent was measured using an Ubbelohde viscometer (manufactured by Rigo Co., Ltd.) adjusted to 30°C, and the intrinsic viscosity [η] was calculated using the following formula. [η]=(-1+√(1+4K'ηSp)) / 2K'C ηSp=(τ-τ0)τ0 in, [η]: Intrinsic viscosity (dl / g) ηSp: Specific viscosity (-) K': Huggins' constant (= 0.33) C: concentration (=1g / dl) τ: Sample drop time (sec) τ0: solvent falling time (sec)

[0113] (2) Content of the specified metal element in the sample The polyester resin was weighed in a platinum crucible, carbonized in an electric heating furnace, and then ashed in a muffle furnace at 550°C for 8 hours. The ashed sample was dissolved in 1.2M hydrochloric acid to prepare a sample solution. The prepared sample solution was measured under the following conditions, and the concentrations of antimony and aluminum in the polyester resin were determined by high-frequency inductively coupled plasma emission spectrometry. Device: CIROS-120 manufactured by SPECTRO Plasma output: 1400W Plasma gas: 13.0L / min Auxiliary gas: 2.0L / min Nebulizer: Cross-flow nebulizer Chamber: Cyclone chamber Measurement wavelength: 167.078nm

[0114] (3) Phosphorus content in polyester resin After wet decomposition of the polyester resin with sulfuric acid, nitric acid, and perchloric acid, ammonia water was used for neutralization. After adding ammonium molybdate and hydrazine sulfate to the prepared solution, the absorbance at a wavelength of 830 nm was measured using an ultraviolet-visible absorptiophotometer (manufactured by Shimadzu Corporation, UV-1700). The concentration of phosphorus in the polyester resin was calculated based on a pre-made calibration curve.

[0115] (4) Acid value The film and the raw material polyester resin were measured by the following method. Sample preparation The film or raw polyester resin is crushed, vacuum dried at 70°C for 24 hours, and weighed using a balance in the range of 0.20±0.0005g. In addition, when measuring the acid value of each layer, a sample in which each layer is extruded as a single layer is made as the sample. Let the mass at this time be W (g). Add 10ml of benzyl alcohol and the weighed sample to the test tube, immerse the test tube in a benzyl alcohol bath heated to 205°C, and dissolve the sample while stirring with a glass rod. The samples with a dissolution time of 3 minutes, 5 minutes, and 7 minutes are designated as A, B, and C, respectively. Next, prepare the test tube again, add only benzyl alcohol, and process it in the same steps, and the samples with a dissolution time of 3 minutes, 5 minutes, and 7 minutes are designated as a, b, and c, respectively.

[0116] Titration Titrate with 0.04 mol / l potassium hydroxide solution (ethanol solution) with known factors in advance. Use phenol red as an indicator, and determine the titration amount (ml) of the potassium hydroxide solution when the color changes from yellow-green to light red. Set the titration amount of samples A, B, and C as XA, XB, and XC (ml). Set the titration amount of samples a, b, and c as Xa, Xb, and Xc (ml). Using the titration amounts XA, XB, and XC for each dissolution time, the titration amount V (ml) when the dissolution time is 0 minutes is calculated by the least square method. Similarly, using Xa, Xb, and Xc, the titration amount V0 (ml) is calculated. Next, the acid value is calculated according to the following formula. Carboxyl terminal concentration (eq / ton) = [(V-V0) × 0.04 × NF × 1000] / W NF: Factor of 0.04 mol / l potassium hydroxide solution

[0117] (5) Quantification of cyclic trimers The sample is frozen and crushed or fragmented, and 100 mg of the sample is accurately weighed. Dissolve it in 3 mL of hexafluoroisopropanol / chloroform mixture (volume ratio = 2 / 3), and further add 20 mL of chloroform to dilute it. After adding 10 mL of methanol to precipitate the polymer, filter it. Evaporate the filtrate to dryness and use 10 mL of dimethylformamide to make the volume constant. Then, quantify the amount of cyclic trimer in the polyester resin or hollow molded body according to the following high performance liquid chromatography. Repeat the above operation 5 times, and set the average value as the CT content. Device: L-7000 (manufactured by Hitachi, Ltd.) Chromatographic column: μ-Bondasphere C185μ100 angstroms 3.9 mm×15 cm (manufactured by Waters) Solvent: Eluent A: 2% acetic acid / water (v / v) Eluent B: acetonitrile Gradient B%: 10→100% (0→55 min) Flow rate: 0.8 mL / min Temperature: 30℃ Detector: UV-259nm

[0118] (6) Elongation at break (TE) The test was carried out in accordance with JIS-C-2318-1997 5.3.31 (tensile strength and elongation). Film test pieces with a width of 10 mm and a length of 190 mm were sampled from the MD direction (longitudinal direction, film winding direction) and the TD direction (transverse direction, direction perpendicular to the MD direction). The film test piece was placed in a tensile testing machine (Tensilon RTC-125A manufactured by ORIENTEC), and stretched at a distance of 100 mm between chucks and a pulling speed of 200 mm / min at a temperature of 23°C and a humidity of 65% RH. The stress required for breaking and the elongation of the film were calculated to obtain the elongation at break (%). The reduction rate of elongation at break is a value obtained by dividing the measured value by the elongation at break of a film produced using only virgin PET of the reference example.

[0119] (7) Carbon content from biomass resources The measurement was carried out by radiocarbon (C14) measurement according to ASTM D6866-16 Method B (AMS).

[0120] PET Manufacturing Bio PET(A1, A2)

[0121] Preparation of ethylene glycol solution containing aluminum A 20 g / L aqueous solution of basic aluminum acetate and an equal amount (volume ratio) of ethylene glycol derived from biomass resources are charged into a preparation tank, and after stirring at room temperature (23°C) for several hours, water is distilled from the system while stirring at 50-90°C for several hours under reduced pressure (3 kPa), to prepare an aluminum-containing ethylene glycol solution s containing 20 g / L of aluminum compound.

[0122] Preparation of ethylene glycol solution containing phosphorus As a phosphorus compound, Irganox 1222 (manufactured by BASF) and ethylene glycol derived from biomass resources were charged into a preparation tank and heat treated at 175° C. for 150 minutes while stirring under nitrogen substitution to prepare a phosphorus-containing ethylene glycol solution t containing 50 g / L of the phosphorus compound.

[0123] Polymerization of PET Bio PET(A1, A2) A polyester oligomer with an esterification rate of about 95% consisting of high-purity terephthalic acid and ethylene glycol derived from biomass resources prepared in advance and high-purity terephthalic acid and high-purity terephthalic acid were charged into a 10L stainless steel autoclave with a stirrer, and an esterification reaction was carried out at 260°C to obtain an oligomer mixture. The concentration of the acid terminal group of the obtained oligomer mixture was 750eq / ton, and the ratio of the hydroxyl terminal (OH%) was 59 mol%. A mixed solution of the aluminum-containing ethylene glycol solution s and the phosphorus-containing ethylene glycol solution t prepared according to the above method was added to the obtained oligomer mixture. The mixed solution was set to 16 mass ppm and 25 mass ppm as aluminum element and phosphorus element, respectively, relative to the mass of the oligomer mixture. After that, the system temperature was raised to 280°C over 1 hour, during which the system pressure was slowly reduced to 0.15 kPa, and polycondensation reaction was carried out under this condition to obtain a polyethylene terephthalate resin having an IV of 0.60 dl / g. The obtained polyethylene terephthalate resin was designated as Bio PET (A1).

[0124] Bio PET (A2) was prepared in the same manner except that the amounts of the aluminum-containing ethylene glycol solution s and the phosphorus-containing ethylene glycol solution t were changed. The properties of Bio PET (A1) and Bio PET (A2) are shown in Table 2.

[0125] Bio PET(A3, A4) The esterification reaction tank is heated, and at the time point of reaching 200°C, 86.4 parts by mass of terephthalic acid derived from petroleum and 64.6 parts by mass of ethylene glycol derived from biomass resources are loaded, and while stirring, 0.017 parts by mass of antimony trioxide, 0.064 parts by mass of magnesium acetate tetrahydrate, and 0.16 parts by mass of triethylamine as catalysts are loaded. Then, pressurization and heating are carried out, and after pressurized esterification reaction is carried out under the conditions of gauge pressure 0.34MPa and 240°C, the esterification reaction tank is restored to normal pressure and 0.014 parts by mass of phosphoric acid are added. Further, it takes 15 minutes to heat up to 260°C, and 0.012 parts by mass of trimethyl phosphate are added. Then, after 15 minutes, a high-pressure disperser is used for dispersion treatment, and the resulting esterification reaction product is transferred to a polycondensation reaction tank, and a polycondensation reaction under reduced pressure is carried out at 280°C. After the polycondensation reaction was completed, the product was filtered using a filter made by Naslon with a 95% cut size of 5 μm, extruded from a nozzle into strands, cooled and solidified using cooling water that had been filtered in advance (pore size: 1 μm or less), and cut into pellets. The resulting polyethylene terephthalate resin was referred to as Bio PET (A3).

[0127] Bio PET (A4) was obtained in the same manner except that the amount of the added catalyst such as antimony trioxide was changed. The properties of Bio PET (A3) and Bio PET (A4) are shown in Table 2.

[0128] Non-Bio PET(B1) It is a product obtained by polycondensing terephthalic acid and ethylene glycol derived from petroleum using an antimony trioxide catalyst. The properties are shown in Table 2.

[0129] [Table 2] BiOPET A1 A2 A3 A4 B1 Ratio of EG derived from biomass resources in used EG (%) 100 100 100 100 0 Carbon content of Bio PET derived from biomass resources (%) >19 >19 >19 >19 - catalyst AI / P AI / P Sb Sb Sb Amount of Al in resin (ppm by mass) 16 21 - - - P content in resin (ppm by mass) 25 45 - - - Sb element content in resin (ppm by mass) - - 135 350 125 IV (dL / g) 0.621 0.667 0.625 0.611 0.62 AV(eq / ton) 32 30 30 31 34 cT amount (mass %) 0.92 0.92 0.92 0.92 0.92

[0130] Production of recycled PET pellets Dried primary pellets were charged into the film production equipment used in the examples, extruded into a sheet in a cooled roll shape using a die under the conditions described in Table 3, and then wound into a roll shape without stretching. The rolled sheet was crushed using a crusher, placed in a flexible container bag, and placed in a non-air-conditioned room for more than one week. After that, the crushed resin was dried under reduced pressure, put into a twin-screw kneading machine, melted and extruded into strands under the conditions described in Table 3, and then fragmented after being cooled with water to obtain pellets of recycled resin. In addition, the melting time in Table 3 is the average time from the region set above the melting point of the film to the die outlet in the extruder, and the value obtained by dividing the total amount of the resin in the extruder obtained by simulation and the amount from the piping to the die outlet by the volume of the resin put in per unit time. The properties of the recovered resin are shown in Table 3.

[0131] [Table 3]

[0132] Film production1 The virgin PET pellets and the recycled PET pellets were mixed, dried under reduced pressure, and then put into the hopper of the film manufacturing equipment, and extruded into a sheet in a cooled roll under the conditions described in Table 3. The obtained sheet was stretched 3.4 times in the longitudinal direction at 90°C using rollers of different circumferences. Then, it was stretched to 3.8 times in the width direction in a tenter heated to 120°C, and then heat-set at 230°C to obtain a biaxially stretched polyester film with a thickness of 40 μm. The results are shown in Table 4. Each reference example was manufactured using only virgin resin. In the examples, even when the amount of recycled resin increases, the difference in IV and AV of the membrane is small compared to the reference example, and the decrease in physical properties (breaking strength) is also small. In particular, in Examples 1 to 6 using Al-based catalysts, the difference in IV, AV, and membrane physical properties is small, and there is almost no concern that problems will occur even when the amount of recycled resin input changes greatly. On the other hand, in the comparative examples, in Comparative Example 1 using 10% by mass of recycled resin, although the IV and AV differences of the film are smaller and the decrease in physical properties (breaking strength) is less compared to the reference example, when the recycled resin is set to 35%, a decrease in IV, an increase in AV, and a decrease in physical properties are confirmed. In order to manufacture films with the same characteristics, there is a limit to the amount of recycled resin input. Furthermore, when the amount of recycled resin input increases, there is a concern that the film is easily deteriorated when exposed to a hot and humid state for a long time, and it is difficult to obtain a film with stable quality from the perspective of durability.

[0133] [Table 4]

[0134] Film manufacturing 2 Using Bio PET (A1) and recycled PET particles (A1-r1) as virgin PET particles, a sheet-like object was obtained in the same manner as in the film manufacturing 1. The obtained sheet-like object was stretched 4.2 times in the width direction in a tenter heated to 120°C, and then heat-set at 200°C to obtain a biaxially stretched polyester film with a thickness of 80 μm. The results are shown in Table 5. Reference Example 5 was manufactured using only virgin resin. It can be seen that the difference in mechanical properties between Example 9 and Reference Example 5 is small, and they have equivalent optical properties. Even when the input amount of recycled resin changes, a film with stable quality is obtained.

[0135] In addition, the refractive indices (nx, ny, where nx < ny) of the orthogonal biaxial axes and the refractive index (Nz) in the thickness direction are determined using an Abbe refractometer (manufactured by ATAGO Co., Ltd., NAR-4T, measurement wavelength 589 nm), and the thickness d (nm) of the film is measured using an electronic micrometer (manufactured by Fine Liu off Co., Ltd., Miritoron1245D). After converting the unit to nm, the Re, Rth, and NZ coefficients are calculated from these values according to the following equations. · Re = (nx - ny) × d · Rth = (nx + ny - 2nz) × d / 2 · NZ coefficient = (ny - nz) / (ny - nx)

[0136] [Table 5] Industrial Applicability

[0137] According to the present invention, in a film using polyethylene terephthalate obtained from biomass resources as a raw material, even when the addition amount of the recycled polyester film changes, a polyester film can be produced in which many characteristics of the resulting film do not change significantly. Even when the production volume changes, a film with a high effect of reducing the environmental burden can be supplied as a film with stable quality, which can greatly contribute to the industry.

Claims

1. A polyester film comprising polyethylene terephthalate produced using ethylene glycol derived from biomass resources and / or terephthalic acid derived from biomass resources, wherein the polyethylene terephthalate produced from the monomer derived from the biomass resources is obtained by polycondensation using an aluminum compound and a phosphorus compound as a catalyst. 2 . The polyester film according to claim 1 , comprising a recycled polyester resin obtained from a film production process. 3 . The polyester film according to claim 2 , wherein the ratio of the recovered polyester film is 5 to 50% by mass of the total polyester resin constituting the film. 4 . The polyester film according to claim 1 , wherein the intrinsic viscosity of the polyester resin constituting the film is 0.52 to 0.73 dL / g. 5 . The polyester film according to claim 1 , wherein the polyester resin constituting the film has an acid value of 5 to 80 dL / g.

6. A method for producing a polyester film, characterized in that: A method for producing a polyester film, comprising the step of producing a polyester film using polyethylene terephthalate produced from ethylene glycol derived from biomass resources and / or terephthalic acid derived from biomass resources as a raw material, wherein unused polyethylene terephthalate produced from monomers derived from biomass resources and recycled polyethylene terephthalate which is a molten molded product discharged from the polyester film production step are melt-mixed and formed into a film. 7 . The method for producing a polyester film according to claim 6 , wherein the amount of the recovered polyethylene terephthalate is 5 to 50% by mass based on the total amount of the unused polyethylene terephthalate produced from the monomer derived from biomass resources and the recovered polyethylene terephthalate. 8 . The method for producing a polyester film according to claim 6 , wherein the polyethylene terephthalate produced from the monomer derived from biomass resources contains an aluminum compound and a phosphorus compound as catalysts. 9 . The method for producing a polyester film according to claim 6 , wherein the difference between the intrinsic viscosity of the unused polyethylene terephthalate produced from the monomer derived from biomass resources and the intrinsic viscosity of the recovered polyethylene terephthalate is 0.1 dL / g or less. 10 . The method for producing a polyester film according to claim 6 , wherein a ratio of the intrinsic viscosity of the unused polyethylene terephthalate produced from monomers derived from biomass resources to the intrinsic viscosity of the recycled polyethylene terephthalate is 0.85 to 1. 11 . The method for producing a polyester film according to claim 6 , wherein the difference between the acid value of the unused polyethylene terephthalate produced from the monomer derived from biomass resources and the acid value of the recovered polyethylene terephthalate is 22 eq / ton or less.

Citation Information

Patent Citations

  • Biaxially stretched polyester film

    WO2022131360A1